2002
DOI: 10.1159/000064461
|View full text |Cite
|
Sign up to set email alerts
|

Acute Interstitial Nephritis Associated with the Use of Mesalazine in Inflammatory Bowel Disease

Abstract: Background: In the last 10 years several reports have linked oral 5-aminosalicylic acid (5-ASA) therapy to acute and chronic tubulointerstitial nephritis, but to our knowledge only 2 patients have been reported with terminal end-stage renal disease due to mesalazine (5-ASA). After 1 year of treatment with 5-ASA annual monitoring of serum creatinine is recommended. Results: We report the development of end-stage renal disease in a patient 10 months after the last assessment of serum creatinine, which was normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 6 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…Table 1 summarizes the 23 biopsy-proven case reports of this complication published in the English literature over the past 13 years. The mean age at diagnosis was 33 years, with the current patient and that of Frandsen et al [14] being the youngest reported patients at 18 years of age. Of the reported patients, 26% had Crohn disease, while 74%, including our patient, had ulcerative colitis.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Table 1 summarizes the 23 biopsy-proven case reports of this complication published in the English literature over the past 13 years. The mean age at diagnosis was 33 years, with the current patient and that of Frandsen et al [14] being the youngest reported patients at 18 years of age. Of the reported patients, 26% had Crohn disease, while 74%, including our patient, had ulcerative colitis.…”
Section: Discussionmentioning
confidence: 44%
“…Over the past decade, more than 30 cases of interstitial nephritis associated with this medication have been described worldwide [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. Only 1 such patient has been 18 years of age or less.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Ulcerative colitis is a disease that occurs in human colon, where thousands of microorganisms reside. But it is not significantly found in germ-free animals.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of side effects such as interstitial nephritis caused by systemic absorption of 5-ASA restrains the use of high doses for treatment [Frandsen et al 2002;Riley et al 1992;Staerk Laursen et al 1990]. About 30% of an oral administration dose of 5-ASA (coated, timereleased or azo-bound) is absorbed, and can potentially cause side effects [Klotz, 1985].…”
Section: In Vivo Investigationmentioning
confidence: 99%